STRUCTURAL DESIGN OF A FIVE-STORY STEEL PARKING BUILDING AT ISLAMIC UNIVERSITY OF NAHDLATUL ULAMA - Mahendra Hamid Arrafi; Muhammad Ilham Amiluddin; Muhammad Adi Sukma; Rizky Maulana; Nor Hidayati (Jurnal Disprotek, 2026)
The increasing number of students at Nahdlatul Ulama Islamic University each year has created an urgent demand for adequate parking facilities. As a result, the construction of a steel-based parking structure becomes an ideal solution to address the limitations of available land. Steel is selected as the primary structural material due to its high shear strength, ease of installation, and efficient connection between structural components. The proposed parking building consists of five floors, with a length of 29.4 meters, a width of 10.95 meters, and a total height of 15 meters. The structural design of this five-story steel parking facility involves a series of analyses and calculations to ensure safety, stability, and compliance with applicable standards. The process includes soil investigation, load determination, structural modeling, and the design of each structural element such as slabs, beams, columns, and foundations. The structural analysis of this building was carried out using SAP2000, which resulted in the selection of IWF 250.250 profiles for beams, IWF 400.400 profiles for the primary columns, and IWF 300.300 profiles for secondary columns. The foundation system is designed using driven pile foundations with a depth of 11 meters. PERENCANAAN STRUKTUR BAJA GEDUNG PARKIR 5 LANTAI UNIVERSITAS ISLAM NAHDLATUL ULAMA Pertumbuhan jumlah mahasiswa Universitas Islam Nahdlatul Ulama yang meningkat setiap tahunnya menyebabkan kebutuhan lahan parkir yang memadai semakin mendesak. Dengan demikian, pembangunan struktur parkir berbahan baja adalah jawaban yang ideal untuk mengatasi masalah keterbatasan lahan. Baja digunakan sebagai bahan kontruksi karena memiliki kekuatan geser yang lebih besar, serta lebih mudah dalam pemasangan dan penghubung antara bagian. Gedung parkir ini memiliki tinggi 5 lantai, dengan panjang 29,4 meter, lebar bangunan 10,95 meter, dan ketinggian 15 meter. Perencanaan struktur baja gedung parkir lima lantai meliputi serangkaian analisis dan desain untuk memastikan bangunan aman, stabil, dan memenuhi standar yang berlaku. Proses ini meliputi analisa tanah, penentuan beban, pembuatan model struktur, serta perhitungan ukuran dan penulangan bagian – bagian struktur seperti lantai, balok, kolom, dan pondasi. Analisa pada gedung parkir ini dilakukan dengan menggunakan SAP2000 yang menghasilkan balok menggunakan profil IWF 250.250, kolom 1 menggunakan profil IWF 400.400, serta kolom 2 menggunakan profil IWF 300.300. Perencanaan pondasi menggunakan pondasi tiang pancang kedalaman 11 m.